Region in Indian history - U.P. History Congress 2006 : University of Lucknow); Mahendra Pratāpa, 1947-; Jafri, Saiyid Zaheer Husain; Lucknow University. Department of Medieval & Modern Indian History (New Delhi : Anamika Publishers & Distributors, 2008)
Transcript of papers presented during the 17th session of U.P. History Congress held in the University of Lucknow on 1st-2nd November, 2006, under the aegis of the Dept. of Medieval & Modern Indian History, chiefly on the history of Uttar Pradesh, India; covers the period from earliest times to the present.
Includes bibliographical references.
English and Hindi.
Keywords: Uttar Pradesh (India) -- History -- Congresses